DESIGNING AN ICONOSTASIS OF AN ORTHODOX CHURCH (Innovation in Woodworking Industry and Engineering design, 2026)
In modern design, non-standard approach is encouraged and there are many unique design solutions. Here however, another approach will be considered which pertains to certain standards – canons – in design. An individual iconostasis project was developed for the needs of the Orthodox Church, in accordance with all the canons and meeting the requirements of the church board. This project also preserves the national cultural heritage by employing the dying craft of woodcarvers. The iconostasis was designed for the church in the village of Vladimirovo, respecting the canons and the traditions in wood carving. A project for a bishop’s throne was also created.